Traumatic Brain Injury in a Pampas Fox (Lycalopex gymnocercus) - Thurow Schulz, Érica; Aranha da Costa, Eduarda; Ramos, Mayara Cristtine; Santos Beanes, Alan; Chagas dos Passos, Marina; da Costa da Silva, Luana Cristina; Rösler, Maria Lucia; França, Raqueli Teresinha (Acta Scientiae Veterinariae, 2024)
Background: The pampas fox (Lycalopex gymnocercus) is a wild canid that occurs in the state of Rio Grande do Sul, Brazil. Environmental changes have brought this animal into proximity with urbanized areas. Therefore, one of the greatest threats to the species is being run over, which is considered the main cause of traumatic brain injury (TBI). Data on the treatment of brain injuries in veterinary medicine, especially in wild animals, is still insufficient, so the guidelines applied here are based on human medicine and small animal medicine. The purpose of this paper is to report the clinical treatment used in a case of TBI in a pampas fox (L. gymnocercus). Case: A 2.5 kg juvenile male pampas fox (L. gymnocercus) was admitted to a Wildlife Rehabilitation Center in Rio Grande do Sul. The patient presented with opisthotonos, in a stupor and a score of 10 on the Glasgow Coma Scale. The animal received clinical treatment, isotonic fluid therapy [lactated Ringer’s solution 50 mL/kg/day], and later, hyperosmolar therapy [hypertonic 3%, 4 mL/kg and mannitol 1g/kg], analgesia [dipyrone 25 mg/kg and meloxicam 0.1mg/kg] and antibiotic therapy [sulfamethoxazole with trimethoprim 20 mg/kg]. Clinical follow-up included blood pressure monitoring and complementary tests such as radiography, ultrasound, blood count and biochemistry. The animal exhibited fractures of the parietal bone, microcytic hypochromic anemia and an increase in the enzymes ALT, AST and CK. Dexamethasone [0.15 mg/kg] was introduced on the eighth day of treatment. This was followed by physiotherapy sessions aimed at encouraging the patient to remain in a standing position. After 55 days, the animal was returned to the wild. Discussion: The Glasgow Coma Scale is used in order to standardize the assessment of the depth and duration of unconsciousness and coma in small animals with TBI, based on a similar table to the one used for humans. Motor activity, brainstem reflexes and levels of consciousness are assessed, generating a score. In this case, the patient scored 10, with a prognosis ranging from poor to guarded. After the occurrence of TBI, edema and hemorrhage add volume to the intracranial space, contributing to an increase in intracranial pressure (ICP). The purpose of TBI treatment is to maintain cerebral blood flow and prevent increases in ICP. To this end, 3% hypertonic fluid therapy was administered, which acts by extracting fluid from the intraparenchymal space into the vascular space, reducing intracranial oedema. By the third day of treatment, the patient had already overcome opisthotonos, but was unable to maintain a standing posture, so the 3% hypertonic solution was replaced by mannitol, which is an osmotic, hyperosmolar diuretic and also acts as a free radical eliminator, helping to improve the stability of the neuronal membrane and further inhibiting the development of cytotoxic edema. Dexamethasone was applied 8 days after the animal’s arrival. The use of glucocorticoids is recommended as an adjuvant treatment in patients that do not respond adequately to the use of mannitol and that are not hyperglycemic. Their use can be beneficial in stabilizing plasma membranes in the CNS, increasing energy supply to CNS tissues, reducing edema, promoting diuresis, reducing the formation of free radicals in the CNS, and reducing the formation of cerebrospinal fluid (CSF). With the end of the drug treatment, the patient was able to remain in sternal decubitus, but still had difficulty standing and walking normally. Physiotherapy sessions were started, such as passive range of movement and stretching of the pelvic limbs, assisted support and exercises to stimulate proprioception by gently brushing the patient’s foot pads, which contributed to its improvement and consequently its return to nature. Keywords: brain injury, running over, TBI, wildlife. Título: Traumatismo cranioencefálico em um Graxaim-do-campo (Lycalopex gymnocercus) Descritores: animais silvestres, atropelamento, lesão encefálica, TCE.